متطلبات نظام المعلومات المحاسبية في تحقيق الاطار المتكامل لادارة الجودة الشاملة - بهاوي, مسعود; بدوية, مهري; هبال, مليكة (University of eloued جامعة الوادي, 2017)
This study aimed to identify the requirements for the application of the accounting information system in achieving the integrated framework for the management of the overall quality of economic institutions, and to achieve the objectives of the study were the design of the questionnaire was distributed to the eye of the senior management of the central administration, the use of the descriptive approach through the study of the analytical content, percentages, duplicates, and alpha test Qrenbakh and other tests in order to access the results of the most important results of the study, the following are some of the institutions of the valley is committed to the application of the philosophy of total quality management standard accounting system effectively, there is a moral relationship between the components of the accounting information system and the degree of achievement of the integrated framework of the Algerian industrial enterprises.
مذكرة ماستر تدقيق محاسبي
Keywords: ادارة الجودة الشاملة،نظام معلومات محاسبي، الادارة الوسطى; Total Quality Management, The accounting information system ,The central administration